Dollarization and the Zimbabwe’s Economy - Sikwila , Mike Nyamazana (Journal of Economics and Behavioral Studies, 2013)
This paper examines the economic impact of the inception of the full dollarization1 in Zimbabwe’s economy after the effects of hyperinflation and an unprecedented depreciation of an exchange rate between 2000 and 2008. Dollarization is a generic word implying the use of any foreign currency as legal tender instead of the domestic currency. An analytical qualitative approach was adopted for this study. The analysis of the benefits and costs of dollarization to Zimbabwe’s economy revealed how dollarization has impacted on the stabilization of Zimbabwe’s economy. This article also highlights the fact that Zimbabwe is not the only country in Africa that has had to resort to adopting foreign currency as legal tender in an effort to remedy macroeconomic imbalances. To our knowledge, there is scant literature on dollarization in Africa and this is the reason why we have chosen to examine the impact of dollarization on Zimbabwe’s economy. In addition, we add to Kurt Schuler’s work (2005) by indicating the other African countries that had adopted dollarization over the years. Furthermore, the study offers support to recent literature that asserts that economic stabilization in these countries resulted from the impact of dollarization. The results of the study revealed that dollarization positively impacts on the country’s economy. In particular, this study is important to policymakers in that it sheds some insight into the importance of a strong currency and stable exchange rate for the stabilization of economies that experienced hyperinflation.